2020
DOI: 10.1101/2020.10.08.20209304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of COVID-19-related risk factors and risk of severe influenza outcomes in cancer survivors: a matched cohort study using linked English electronic health records data

Abstract: Background People with active cancer are recognised as at risk of COVID-19 complications, but it is unclear whether the much larger population of cancer survivors is at elevated risk. We aimed to address this by comparing cancer survivors and cancer-free controls for (i) prevalence of comorbidities considered risk factors for COVID-19; and (ii) risk of severe influenza, as a marker of susceptibility to severe outcomes from epidemic respiratory viruses. Methods We included survivors (≥1 year) of the 20 most com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…The difference between COVID-19 and non-COVID mortality risk was less stark in haematological cancer survivors, in keeping with evidence that these cancers are likely associated with a larger raised risk of COVID-19 death. [ 4 , 24 ] Chronic liver disease also showed a smaller association with COVID-19 death compared with non-COVID death, perhaps again reflecting shielding behaviour or social interactions during the pandemic; unfortunately we lacked the data to investigate the role of alcohol in this association. Dementia was associated with disproportionately raised risks of COVID-19 death, but this appeared to be driven by data from wave 1 of the pandemic, likely due to significant outbreaks in residential care homes during that period; by wave 2, dementia was associated with similar risks of COVID-19 and non-COVID death.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between COVID-19 and non-COVID mortality risk was less stark in haematological cancer survivors, in keeping with evidence that these cancers are likely associated with a larger raised risk of COVID-19 death. [ 4 , 24 ] Chronic liver disease also showed a smaller association with COVID-19 death compared with non-COVID death, perhaps again reflecting shielding behaviour or social interactions during the pandemic; unfortunately we lacked the data to investigate the role of alcohol in this association. Dementia was associated with disproportionately raised risks of COVID-19 death, but this appeared to be driven by data from wave 1 of the pandemic, likely due to significant outbreaks in residential care homes during that period; by wave 2, dementia was associated with similar risks of COVID-19 and non-COVID death.…”
Section: Discussionmentioning
confidence: 99%
“…within the infected human being. All human beings with comorbidity or medical illness are at high risk to get an infection than normal or healthy people [ 10 12 ]. From the statistical data, this is reported that the patients with COVID-19 having comorbidity like kidney disease and type-2 diabetes were transferred to hospital with intensive or critical care unit [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…O presente estudo é uma contribuição para a elaboração do plano nacional de vacinação, mas não deve ser considerado isoladamente, pois existem outros fatores de risco que não foram considerados por não constarem nas bases de dados disponíveis (em pelo menos uma das bases utilizadas nas análises), como, por exemplo, cirrose hepática 32 , doença falciforme 33 , síndrome de Down 34 e câncer 35,36 . Existem evidências também de maior morbidade e mortalidade por doenças de transmissão respiratória em populações como a de indígenas 37 e de privados de liberdade 38 .…”
Section: Discussionunclassified